IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE AND CSR IN INDONESIA BUSINESS PRACTICES: LEGAL AND ETHICAL ANALYSIS - Muhamad Handi Wijaya; Agus Satory (CV. ADIBA AISHA AMIRA, 2025)
This study examines the implementation of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) in Indonesia, focusing on legal and ethical aspects. The research addresses the problem of weak governance and ceremonial CSR practices, particularly in small and medium enterprises (SMEs). Using a qualitative descriptive approach with secondary data from company reports and academic journals, the study analyzes GCG and CSR practices in large companies and SMEs. Findings indicate that large companies like Unilever implement robust GCG, while SMEs lack formal structures. Strategic CSR enhances reputation, but SMEs often engage in short-term philanthropy. Regulations support implementation, but enforcement is weak. Ethical practices rooted in Pancasila are crucial, yet challenges like corruption persist. The study recommends strengthening regulations and ethics education to enhance GCG and CSR effectiveness.